2002
DOI: 10.1161/01.cir.0000021121.26290.2c
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Human Heat Shock Protein 60 in the Plasma of British Civil Servants

Abstract: Background-TheWhitehall cohort studies (I and II) of British civil servants have identified sociodemographic, psychosocial, and biological risk factors for coronary heart disease (CHD). To identify mechanisms responsible for susceptibility to CHD, specific biological markers of stress are increasingly being measured. One marker linked to susceptibility to CHD is heat shock protein (Hsp) 60. Methods and Results-Blood was taken from 229 civil servants (126 men and 103 women) in the Whitehall II cohort drawn equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 23 publications
5
98
1
1
Order By: Relevance
“…In these instances, stressors such as surgical operations [25], intense physical exercises [15,28,85], and short-run psychological stress [16,31] were shown to induce extracellular Hsp70. An extracellular elevation of another kind of chaperon (Hsp60) was also shown to be induced by long-term psychosocial stress [46]. In our previous study, the significant prompt (i.e.…”
Section: Possible Role Of Salivary Hsp70 Under Stress Conditionsmentioning
confidence: 88%
“…In these instances, stressors such as surgical operations [25], intense physical exercises [15,28,85], and short-run psychological stress [16,31] were shown to induce extracellular Hsp70. An extracellular elevation of another kind of chaperon (Hsp60) was also shown to be induced by long-term psychosocial stress [46]. In our previous study, the significant prompt (i.e.…”
Section: Possible Role Of Salivary Hsp70 Under Stress Conditionsmentioning
confidence: 88%
“…More specifically, heightened cardiovascular reactivity could reflect sympathetic hyperresponsivity or enhanced vagal withdrawal during stress, whereas poorer cardiovascular recovery could be due to prolonged sympathetic activation, diminished vagal tone, or attenuated or delayed vagal rebound following the termination of stress 33 . In addition, several studies have reported associations between psychosocial variables and vascular function 34,35 , inflammation 36 , increased blood clotting and decreased fibrinolysis 37,38 . Reasons for exclusion n = 150 excluded articles n = 100 excluded articles n = 90 quasi-experiments (7 *) n = 22 reviews (5 *) n = 22 crossectional (3 *) n = 7 case-controls (1 *) n = 2 ecological (1 *) n = 2 comments n = 2 clinical trials n = 1 book n = 1 case study n = 1 test-retest Exposure n = 36 occupational (7 *) n = 7 pos-traumatic (2 *) n = 6 stability (2 *) n = 3 hospital internment (2 *) n = 3 risk groups n = 2 financial situation (1 *) n = 2 meditation n = 1 corporal mass n = 1 lifestyle Random effect model, odds ratio for increased blood pressure ≥ 3.5mmHg/hipertension of the effect of responses to stressor tasks in 23 comparison groups from 6 prospective cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This is a million-fold range, and this range of levels encompasses both the anti-and pro-inflammatory effects of these proteins. The author's group have shown a relationship between circulating Hsp60 and cardiovascular disease, and this may relate to the influence of these proteins on macrophage function (Lewthwaite et al 2002b;Halcox et al 2005;Shamaei-Tousi et al 2007b) The in vivo breakdown of bone is driven by a specific monocyte population known as the osteoclast. Gramnegative bacterial Hsp60 proteins have been shown to stimulate both osteoclast formation and activation (Kirby et al 1995;Reddi et al 1998) as has human Hsp60 (Meghji et al 2003).…”
Section: Hsp60mentioning
confidence: 99%